1995
DOI: 10.1021/jm00017a021
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Effects on Retinoid Receptor Selectivity. 2. Effects of Retinoid Bridging Group on Retinoid X Receptor Activity and Selectivity

Abstract: The natural retinoid 9-cis-retinoic acid is an activating ligand for both the retinoic acid receptors (RARs) and the retinoid X receptors (RXRs), which are members of the retinoid/thyroid hormone/steroid hormone family of nuclear receptor proteins that activate gene transcription through specific response elements. The pharmacophoric groups necessary to confer RXR selectivity were established by evaluating the ability of 21 conformationally restricted retinoids to activate the TREpal retinoic acid receptor res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 18 publications
1
70
0
Order By: Relevance
“…We investigated whether 9-cis-4-oxo-RA is a non-RXR agonist in RAR-RXR heterodimers, using the RXR-specific agonist SR11246 (36). Similarly as reported in investigations in cell lines (10)(11)(12), SR 11246 alone failed to cause significant activation of a DR-5 RA response element containing reporter via endogenous RARs and RXRs in early Xenopus embryos, but caused synergistic activation when combined with RAR-specific ligands [RA, 4-oxo-RA, or the RAR␣-specific (at suboptimal concentrations) ligand Am80] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We investigated whether 9-cis-4-oxo-RA is a non-RXR agonist in RAR-RXR heterodimers, using the RXR-specific agonist SR11246 (36). Similarly as reported in investigations in cell lines (10)(11)(12), SR 11246 alone failed to cause significant activation of a DR-5 RA response element containing reporter via endogenous RARs and RXRs in early Xenopus embryos, but caused synergistic activation when combined with RAR-specific ligands [RA, 4-oxo-RA, or the RAR␣-specific (at suboptimal concentrations) ligand Am80] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that 9cUAB30 compared well with Targretin in its capacity to prevent mammary cancer (21)(22)(23)(24)(25). The in vitro studies presented here also show how similar each rexinoid is in blocking ErbB2-oncogenic transformation, consistent with in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although 9cUAB30 is slightly less potent than Targretin or 9cRA, it displays a higher degree of RXR selectivity. 9cUAB30 has also been shown to be effective in cancer prevention models (21)(22)(23)(24)(25). 9cUAB30 is a tissue-selective RXR agonist; it does not act as an agonist in liver to activate lipid biosynthesis although it has agonist capabilities in cancer cells (26).…”
mentioning
confidence: 99%
“…RAR␣, ␤ and ␥ as well as RXR selective retinoids have been reported by a number of groups. 19,[25][26][27][28][29][30][31] These retinoids display selectivity in terms of their binding and transactivation of the retinoid receptor classes and subclasses. The advantages of these receptor selective retinoids, when compared to the natural retinoids, include their enhanced stability, reduced toxicity and activity in cells which display resistance to RA and 9-cis-RA.…”
Section: Retinoid Receptorsmentioning
confidence: 99%